A Study Of Early Buddhist Institute Of Nuns (Bhikkhunīs) Based On The Pātimokkha - Shatsena, Chatsumarn (My University, 1970)
This dissertation presents the analytical discussion on the formation of the early Buddhist institute of nuns (Bhikkhuni Sangha) and various arguments arising there from, including the examination on the accusation against Ananda in the First Council. The main inquiry, however lies in the comparative study of the monastic rules of the nuns (Bhikkhuni Pātimokkha). The materials are from various available sources which enable one to proceed more fruitfully in obtaining new information and findings. The monastic rules for Buddhist nuns of different schools are substantially the same, reaffirming the belief that different Buddhistic schools are in unity, the differences lie mainly in philosophical and metaphysical expositions. The study on the internal aspects of the early Buddhist institute of nuns shows the importance of the co-existence of the doctrine and the monastic rules. One who aims at the spiritual attainment must keep in mind the balance of these two principles, i.e., wisdom and practice.
Keywords: Religion; Religion